A Simple and Effective Way to Study Executive Functions by Using 360° Videos - Borgnis, Francesca; Baglio, Francesca; Pedroli, Elisa; Rossetto, Federica; Riva, Giuseppe; Cipresso, Pietro (Frontiers in Neuroscience, 2021)
The executive dysfunctions constitute a significant public health problem due to their high impact on everyday life and personal independence. Therefore, the identification of early strategies to assess and rehabilitate these impairments appears to be a priority. The ecological limitations of traditional neuropsychological tests and numerous difficulties in administering tests in real-life scenarios have led to the increasing use of Virtual reality and 360°environments-based tools for assessing executive functions (EFs) in real-life. This perspective aims at proposing the development and implementation of Executive-functions Innovative Tool 360° (EXIT 360°), an innovative, enjoyable and ecologically valid tool for a multidimensional and multicomponent evaluation of executive dysfunctions. EXIT 360° allows a complete and integrated executive functioning assessment through an original task for EFs delivered via a Mobile-powered VR headset combined with ET and EEG. Our tool is born as a 360°-based instrument, easily accessible and clinically usable, that will radically transform clinicians’ and patient's assessment experience. In EXIT 360°, patients are engaged in a “game for health” where they must perform everyday subtasks in 360° daily life environments. In this way, the clinicians can obtain quickly more ecologically valid information about several aspects of EFs (e.g., planning, problem-solving). Moreover, the multimodal approach allows completing EFs’ assessment by integrating verbal responses, reaction times and physiological data (eye-movements and brain activation). Overall, EXIT 360° will allow obtaining simultaneously and in real-time more information about executive dysfunction and its impact in real-life, allowing clinicians to tailor the rehabilitation to the subject’s needs.